High-Normal Glucose Levels in a Routine Oral 1-Hour 50 g Glucose Challenge Test Are Associated with a Poorer Glycemic Status Later in Life - Yoles, Israel; Baevsky, Tuvia; Rosenberg, Reena; Shevy, Menashe (American Journal of Perinatology, 2017)
Objective A 1-hour 50 g glucose challenge test (GCT) is generally used as a screening test for a 3-hour 100 g test. The future glycemic status of a pregnant woman with abnormal (high) GCT is widely discussed in the literature. On the other hand, future glycemic status of women with various glucose levels within the normal range on GCT has not yet been studied. To examine the hypothesis that lower glucose levels in GCT may result in a better glycemic status later in life, we compared the glucose levels in GCT with the glycemic status 9 years later in a large cohort in Israel.Study Design The study was performed at the Central District of Clalit Health Services, the largest health maintenance organization in Israel. From the computerized database, we gathered data on women who underwent GCT between August 2005 and August 2006.We evaluated the association between GCT results at entry and fasting glucose levels 9 years later. The study was approved by the institutional review board (IRB). We used analysis of variance (ANOVA) followed by pairwise comparisons using Tukey's method (p = 0.05) and ordinal logistic regression tests for statistical analysis.Results A total of 6,929 women performed GCT at entry. Fasting glucose levels were available 9 years later for 4,247 women. GCT results at entry level were grouped and divided into the following groups: very low GCT (<100 mg%), low-normal (100–125 mg%), high-normal (126–140 mg%), and abnormal GCT (>140 mg%). Fasting glucose results, as well as impaired fasting glucose 9 years following normal GCT had a direct correlation with GCT results. Ten percent of women who performed GCT had a high-normal result of 126 to 140 mg%. This high-normal group had a significantly higher fasting glucose and impaired fasting glucose (>100 mg%) 9 years after performing the GCT as compared with the very low or normal GCT groups. Moreover, diabetes risk of this group was significantly higher than the lower groups.Conclusion Although GCT is only a screening test, it may serve as a practical predictor for further fasting glucose levels, impaired fasting glucose, and diabetes in a relatively short time (9 years). In this study, women with GCT levels up to 125 mg%, when tested 9 years later, had significantly lower fasting glucose and lower percentage of impaired fasting glucose and diabetes than those with GCT above 126 mg%. Women with “normal” GCT levels between 126 and 140 mg% should be closely monitored for their further glycemic status.
Keywords: glucose challenge test; normal GCT; prediabetes; diabetes